2024
DOI: 10.3390/cells13030230
|View full text |Cite
|
Sign up to set email alerts
|

Ergothioneine Prevents Neuronal Cell Death Caused by the Neurotoxin 6-Hydroxydopamine

Saho Yuzawa,
Motonari Nakashio,
Suzuna Ichimura
et al.

Abstract: Neuronal cell death is a key mechanism involved in the development and exacerbation of Parkinson’s disease (PD). The excessive production of reactive oxygen species (ROS) is a major cause leading to neuronal death; therefore, compounds that prevent oxidative stress-dependent neuronal death may be promising as a preventive method for PD. Ergothioneine is a natural amino acid with antioxidant properties, and its protective functions in the body are attracting attention. However, there has been no investigation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…VHCL inhibited the protective effect of ET on mitochondrial dysfunction. Our results add to previous findings that ET has neuroprotective functions [ 21 , 26 , 28 , 43 ] which could potentially aid in the prevention and treatment of PD. We would also like to acknowledge the paper that was published by Yuzawa et al (2024) [ 43 ] while we were preparing this manuscript.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…VHCL inhibited the protective effect of ET on mitochondrial dysfunction. Our results add to previous findings that ET has neuroprotective functions [ 21 , 26 , 28 , 43 ] which could potentially aid in the prevention and treatment of PD. We would also like to acknowledge the paper that was published by Yuzawa et al (2024) [ 43 ] while we were preparing this manuscript.…”
Section: Discussionsupporting
confidence: 86%
“…Our results add to previous findings that ET has neuroprotective functions [ 21 , 26 , 28 , 43 ] which could potentially aid in the prevention and treatment of PD. We would also like to acknowledge the paper that was published by Yuzawa et al (2024) [ 43 ] while we were preparing this manuscript. Yuzawa et al reported the protective effect of ET against 6-OHDA neurotoxin in immortalised mouse hypothalamic cells (GT-17), a cell line perhaps less relevant to PD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation